2003
DOI: 10.3904/kjim.2003.18.3.146
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction and Their Relation to Cardiovascular Risk Factors such as Lipid Profile, hsCRP, and Waist Hip Ratio in Korea

Abstract: BackgroundThyroid abnormalities affect a considerable portion of the population, and overt hypothyroidism is associated with an elevated risk of cardiovascular disease and adverse changes in blood lipids. Subclinical hypothyroidism is also associated with an increase risk of cardiovascular disease. So, we undertook this study to investigate the prevalence of overt and subclinical thyroid disorders and their associations with cardiovascular risk factors.Methods:This study involved 66260 subjects (43588 men, 226… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 37 publications
8
55
1
1
Order By: Relevance
“…Jung 16 found mean plasma total cholesterol and LDL cholesterol levels elevated in hypothyroid cases than in normal controls. In another study, average serum total cholesterol level was found elevated in primary and secondary hypothyroidism 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Jung 16 found mean plasma total cholesterol and LDL cholesterol levels elevated in hypothyroid cases than in normal controls. In another study, average serum total cholesterol level was found elevated in primary and secondary hypothyroidism 17 .…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43][44] Conflicting results have been obtained in relation to hsCRP: three studies showed some correlation, [44][45][46] while another three did not show any association at all. 39,47,48 The positive studies tended to include patients with definitive thyroid disease, as opposed to asymptomatic patients who had been found through screening. For example, the study by Christ-Crain et al 43 compared 63 women with subclinical hypothyroidism with 61 women with overt hypothyroidism and 40 euthyroid controls, but more than 40% of the women with subclinical hypothyroidism had been treated with radioiodine, surgery or anti-thyroid drugs for either for Graves disease or for toxic multinodular goiter.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported varied types of dyslipidemias in hypothyroid patients viz; hypercholesterolemia, elevation of very low density lipoprotein (VLDL), hypertriglyceridemia etc. Jung et al found mean plasma total cholesterol and LDL cholesterol levels elevated in hypothyroid cases than in normal controls (202.1 mg/dl and 121.8 mg/dl versus 197.1 mg/dl and 120.1 mg/dl, respectively) [18]. In another study, average serum total cholesterol level was found elevated in primary and secondary hypothyroidism [19].…”
Section: Conclusion:-mentioning
confidence: 97%